A Systematic Review of Mobile Learning-Based Research in Fostering Critical Thinking Skills - Darlin, Darlin; Arianto, Fajar; Martadi, Martadi; Laha, M. Saleh; Nurlin, Nurlin; Nisa’, Khoirun (Studies in Learning and Teaching, 2026)
Critical thinking skills are essential competencies in the 21st century, so this study aims to present a systematic literature review on the role of mobile learning (m-learning) in fostering it at the higher education level by identifying trends, methodologies, effectiveness, and challenges. Following PRISMA guidelines, 20 articles from the Scopus database (2020-2025) were qualitatively analyzed. The results consistently show that m-learning interventions, especially when synergized with pedagogical models such as Problem-Based Learning (PBL), have proven significantly effective in improving students' critical thinking skills. Trend analysis reveals a geographic dominance of research from Indonesia (48.1%), with peak research productivity occurring in 2022 and dominated by R&D and quantitative approaches in the context of higher education in the fields of science and vocational studies. Despite this effectiveness, the main challenges identified are the low development of inference sub-skills and the risk of shallow learning. In conclusion, m-learning is a valid strategy; however, future research is recommended to move beyond proof-of-concept studies by focusing on increasing methodological rigor, investigating specific mechanisms between technology features and cognitive sub-skills, and expanding the research context to other disciplines to test the generalizability of the findings.